Youthful commentary on a growth economy : soundings from New Zealand 1884-1914 - Olson, Sherry; Holland, Peter (Enfances, Familles, Générations, 2017)
Research Framework  : Over the thirty years before World War I, expansion of the world economy occasioned new opportunities and new constraints for children and adolescents as well as adults; but experiences and responses of minors are understated in print sources. Objectives : To discover what societal changes young people noticed and talked about, we examined the « children's page » of a weekly newspaper available for a rural setting in the South Island of New Zealand. The perspective of youth is essential to interpret trajectories inferred from the more conventional sources available in a North American urban setting (Montreal, Quebec). Methodology : From the internet archive PapersPast we collected 12,000 letters of young people aged six through nineteen years, 1886-1909, and extracted their comments on two popular topics : the work they reported (paid or unpaid) and their accounts of toothache.Results : The letters inform us about tasks of young people by age, gender, season, daily routine and household structure. Changes in work assignments at ages 12 to 14, coincident with a spurt of growth and, for most, the end of formal schooling, evoked discussion among them about gender roles and, among girls, protest of the scheduling of their growing up.Conclusion : The seasonality of tasks assigned to children still in school indicates an unrecognized contribution to the elasticity of the rural economy on a global frontier of the industrial food supply. Reallocation of the labour of young people was an ongoing process, subject to negotiation.Contribution : The wealth of information and opinion accessed in the letters invites further experiment with newspaper content analysis for recognizing the participation of segments of the population whose contributions to economic growth have been underestimated.